1992
DOI: 10.1017/s1049023x00039741
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Reanimatology Potentials: A Structured Interview Study in Armenia. III. Results, Conclusions, and Recommendations

Abstract: National medical responses to catastrophic disasters have failed to incorporate a resuscitation component.Purpose:This study sought to determine the lifesaving potentials of modern resuscitation medicine as applied to a catastrophic disaster situation. Previous articles reported the preliminary results (I), and methodology (II) of a structured, retrospective interview study of the 1988 earthquake in Armenia. The present article (III) reports and discusses the definitive findings, formulates conclusions, and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Trauma was the most common cause of death. Pretto et al 8 suggested that deaths might have been prevented if the victims had received medical attention in the first 6 hours after the earthquake. Safar, 24 studying the 1980 earthquake in Italy, concluded that 25% to 50% of victims who were injured and died slowly could have been saved if lifesaving first aid had been rendered immediately.…”
Section: E P I D E M I O L O G I C a N A L Y S I S O F E A R T H Q U mentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma was the most common cause of death. Pretto et al 8 suggested that deaths might have been prevented if the victims had received medical attention in the first 6 hours after the earthquake. Safar, 24 studying the 1980 earthquake in Italy, concluded that 25% to 50% of victims who were injured and died slowly could have been saved if lifesaving first aid had been rendered immediately.…”
Section: E P I D E M I O L O G I C a N A L Y S I S O F E A R T H Q U mentioning
confidence: 99%
“…7 Although studies related to earthquakes are abundant, few of them have focused on the analysis of emergency care needs to reduce mortality and morbidity. For example, Pretto et al 8 reported that deaths might have been prevented if victims had received appropriate medical attention in the first 6 hours after the Armenia earthquake. Schultz et al 9 indicated that response time is critical in the administration of emergency medical care and that special field hospitals established 1 week or more after the earthquake would be too late to prevent early mortality.…”
Section: Introductionmentioning
confidence: 99%
“…We considered that patients arrive to the closest hospital during a period of 4 days after the earthquake in accordance to the evidence from previous earthquakes. 39,61 Thus, in the flow model the demand-supply variable b i (t)…”
Section: Earthquake Casualty Modelingmentioning
confidence: 99%
“…Because these individuals are often at the highest risk, human and economic resources should be allocated to enhance their survival and promote their well being during a catastrophe. Pretto et al (1992Pretto et al ( , 1994 demonstrated that there were many victims whose deaths might have been prevented if they had received medical attention in the first 6 h after the tremor. Safar (1986) showed that about 25-50% of the patients could have been saved if emergency care had been rendered at once.…”
Section: Background Of Motivationmentioning
confidence: 99%